Prenatal diagnosis of mosaic tetrasomy 18p - Silva, Marisa (2014)
To report the case of a prenatally detected de novo mosaic tetrasomy 18p where a combination of different methodologies was used,including conventional cytogenetics and molecular genetics techniques. METHOD: Molecular rapid aneuploidy diagnosis, by quantitative fluorescent polymerase chain reaction (QF-PCR), conventional cytogenetics and fluorescence in situ hybridization (FISH). RESULTS:Amniocentesis was performed at 22 + 5 gestational weeks, on a 37-year-old woman, due to ultrasound detection of fetal interventricular communication, overlapped fingers and unilateral club foot. Molecular rapid aneuploidy testing, by QF-PCR, showed highly increased ratios for markers on the short arm of chromosome 18. Cytogenetic analysis revealed a male karyotype with mosaicism involving two cell lines: one with a supernumerary isochromosome 18p and another with two extra derivative chromosomes 18. Parental karyotypes were normal and QF-PCR analysis indicated that the extra chromosome 18p material was of maternal origin. After counseling the couple opted for pregnancy termination. Anatomopathological studies, as well as further characterization of the derivative chromosomes, are underway in order to provide more accurate genotype-correlation. CONCLUSIONS: The majority of tetrasomy 18p reported cases were ascertained postnatally, had a de novo occurrence and an isochromosome 18p in all cells examined. Prenatal diagnoses of mosaic tetrasomy 18p are, on the other hand, rarely described in the literature. The case herein reported, where a mosaic is present and none of the cell lines is chromosomally normal, may provide further insight on this rare syndrome and help in the knowledge of the associated phenotype. The application of a combined strategy, using QF-PCR, conventional cytogenetics and FISH analysis allowed not only for the identification of the extra chromosome 18p material, in the form of a mosaicism involving isochromosome 18p, but also for determining its parental origin. This information is of particular importance in recurrence risk assessment and therefore crucial for genetic counseling.